Comprehensive analysis reveals CCDC60 as a potential biomarker correlated with prognosis and immune infiltration of head and neck squamous cell carcinoma - Liu, Zhixin; Chen, Shuai; Jia, Wenming; Qian, Ye; Yang, Xiaoqi; Zhang, Minfa; Fang, Tianhe; Liu, Heng (Frontiers in Oncology, 2023)
Background Coiled-coil domain containing 60 (CCDC60) is a member of the CCDC family, which participates in the progression of many types of cancer. However, the prognostic value of CCDC60 in head and neck squamous cell carcinoma (HNSC) and its function in tumor immunity remain unclear. Methods CCDC60 expression and its prognostic potential in HNSC were evaluated by bioinformatics approaches, which was validated in human HNSC samples. Genetic alteration analysis of CCDC60 and the underlying biological function of CCDC60 related co-expressed genes in HNSC were analyzed. The impact of CCDC60 on the regulation of immune infiltration in HNSC was comprehensively investigated. In vitro, a series of functional assays on CCDC60 were performed in HNSC cells. Results Our study has indicated that compared with the adjacent normal tissues, CCDC60 expression was considerably downregulated in HNSC tissues. High CCDC60 expression was connected with favorable outcome of HNSC patients, and its prognostic significance was examined by distinct clinical characteristics. We identified the CCDC60-related co-expression genes, which were mainly enriched in the NOD-like receptor signaling pathway associated with the inhibition of tumor growth, leading to a better prognosis of HNSC patients. In vitro, CCDC60 overexpression significantly inhibited the growth, migration and invasiveness but regulated cell cycle progression, and promoted cell adhesion of Fadu and Cal27 cells. Additionally, high CCDC60 expression had strong connections with the infiltrating levels of immune cells, immune marker sets, immunomodulators and chemokines in HNSC, suggesting that targeting CCDC60 could be a promising strategy to enhance the efficacy of immunotherapy for HNSC patients. Conclusion Tumor suppressor CCDC60 may be identified as a prognostic and immune-related indicator in HNSC, which had the potential functions in regulating the immune infiltration of HNSC and improving the response to immunotherapy for HNSC patients.